Altered Brain Function in Drug-Naïve Major Depressive Disorder Patients With Early-Life Maltreatment: A Resting-State fMRI Study - Xu, Zhexue; Zhang, Jing; Wang, Di; Wang, Ting; Zhang, Shu; Ren, Xi; Zhu, Xiaolei; Kamiya, Atsushi; Fang, Jiliang; Qu, Miao (Frontiers in Psychiatry, 2019)
Childhood Maltreatment (CM) is an important risk factor for major depressive disorder (MDD). Previous studies using emotional task-state functional magnetic resonance (task-state fMRI) found that altered brain function in prefrontal-limbic regions was the key neuropathological mechanism in adult MDD patients with experience of early-life maltreatment. However, to our best knowledge, there is no published study investigating brain function in MDD patients with CM experience using resting-state fMRI (rs-fMRI). In present study, we aimed to detect altered resting-state brain activity in MDD patients with CM experience, and identify significantly activated brain regions, which may provide new insights into the neural mechanism underlying the relationship between MDD and CM experience. The results showed MDD patients with CM experience were associated with increased amplitude of low-frequency fluctuation (ALFF) and altered function connection (FC) in prefrontal cortex when compared to MDD patients without CM. Of note, left frontal middle gyrus (LFEG) was found as a specific brain region which differentiate MDD patients with CM from patients without CM. These results suggest that rs-fMRI is a useful method in studying correlation between MDD and CM experience and altered function of LFEG in resting-state may explain the correlation between MDD and CM experience.